A Systematic Bibliometric Analysis of Value Chain Literacy for Competitive Advantage: Trends and Future Perspectives (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to explore the literature related to value chain literacy and its impact on competitive advantage through a systematic bibliometric analysis approach. In an era of globalization and fierce competition, a deep understanding of how to manage and optimize value chains is essential for companies looking to achieve and maintain a competitive advantage. Using the Scopus database, this study identifies research trends, main topics, and main contributions in this field over the past decade, namely from 2015-2024 with an initial total of 1,097 documents before the screening process. The bibliometric analysis carried out included an evaluation of the distribution of publications, leading authors, institutions, and the most productive countries in 36 documents according to the criteria. In addition, this article uses citation analysis and co-citations to identify key articles and intellectual networks formed around the topic of value chain literacy and competitive advantage. The findings of this study reveal that there has been a significant increase in the number of related publications, with a growing focus on the role of digital technology, innovation, and global integration in optimizing the value chain. The results of the study were able to identify several less explored areas that have the potential to become future research topics, such as the impact of climate change on value chain management and the role of artificial intelligence in improving value chain efficiency. The findings provide a future perspective on how value chain literacy can continue to develop and provide added value for companies in achieving competitive advantage.